Unusual bleeds, unusual clots - Moll, S. (Hämostaseologie, 2007)
Nine unusual bleeding and clotting disorders (or mimickers of such) are described in the format of case presentations, with focus on clinical history, images and diagnostic tests, followed by a discussion of the disease itself and a summarizing clinical teaching point. The disease entities discussed are acquired factor VIII inhibitor, acquired von Willebrand factor inhibitor, haemophilic pseudotumour, Gardner-Diamond syndrome, coumarin-induced skin necrosis, purple toe syndrome, brachiocephalic vein thrombosis with breast enlargement, and leg swelling due to nephrogenic fibrosing dermopathy and lymphoedema. The publication is meant to demonstrate the fascination of clinical coagulation.
Keywords: Coagulation; bleeding; thrombosis; vena cava syndrome; nephrogenic fibrosing dermopathy; warfarin skin necrosis; lymphoedema; factor VIII inhibitor; pseudotumour; haemophilia; von Willebrand factor inhibitor; Gardner Diamond syndrome; purple toe syndrome; brachiocephalic vein thrombosis; superior vena cava syndrome